Adaptation and Implementation of a Family Caregiver Skills Training Program: From Single Site RCT to Multisite Pragmatic Intervention. Issue 1 (9th September 2019) - Shepherd‐Banigan, Megan; Kaufman, Brystana G.; Decosimo, Kasey; Dadolf, Joshua; Boucher, Nathan A.; Mahanna, Elizabeth P.; Bruening, Rebecca; Sullivan, Caitlin; Wang, Virginia; Hastings, S. Nicole; Allen, Kelli D.; Sperber, Nina; et al.
Abstract: Purpose: We describe an approach to rapidly adapt and implement an education and skills improvement intervention to address the needs of family caregivers of functionally impaired veterans—Helping Invested Families Improve Veterans' Experience Study (HI‐FIVES). Design: Prior to implementation in eight sites, a multidisciplinary study team made systematic adaptations to the curriculum content and delivery process using input from the original randomized controlled trial (RCT); a stakeholder advisory board comprised of national experts in caregiver education, nursing, and implementation; and a veteran/caregiver engagement panel. To address site‐specific implementation barriers in diverse settings, we applied the Replicating Effective Programs implementation framework. Findings: Adaptations to HI‐FIVES content and delivery included identifying core/noncore curriculum components, reducing instruction time, and simplifying caregiver recruitment for clinical settings. To enhance curriculum flexibility and potential uptake, site personnel were able to choose which staff would deliver the intervention and whether to offer class sessions in person or remotely. Curriculum materials were standardized and packaged to reduce the time required for implementation and to promote fidelity to the intervention. Conclusions: The emphasis on flexible intervention delivery and standardized materials has been identified as strengths of the adaptation process. Two key challenges have been identifying feasible impact measures and reaching eligible caregivers for intervention recruitment. Clinical Relevance: This systematic implementation process can be used to rapidly adapt an intervention to diverse clinical sites and contexts. Nursing professionals play a significant role in educating and supporting caregivers and care recipients and can take a leading role to implement interventions that address skills and unmet needs for caregivers.